2022
DOI: 10.4018/ijegr.305230
|View full text |Cite
|
Sign up to set email alerts
|

From Bureaucracy to Citizen-Centricity

Abstract: Organisations, including public service organisations, are increasingly adopting a digital transformation strategy, and deploying digital capabilities to enhance customer experience. However, digital initiatives in public services often focus more on the technology with relatively less regard to the citizen for whom the services are designed. To address this lacuna, this study contextualises the digital transformation of public services by focusing on the citizen. This study is based on data collected in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 41 publications
(7 reference statements)
0
13
0
Order By: Relevance
“…Artificial intelligence (AI) in public administration as part of digital transformation initiatives can drive efficiency and intelligence in public service delivery [12]. In addition, the shift from bureaucracy to citizen centricity, facilitated by digital transformation, has led to the deployment of digital capabilities to improve customer experience in public service organizations [14]. Research has demonstrated that implementing collaborative governance in digital transformation may enhance the public value of services by altering the ways in which the government and society interact.…”
Section: Benefits Of Digitalization In Public Service Deliverymentioning
confidence: 99%
See 4 more Smart Citations
“…Artificial intelligence (AI) in public administration as part of digital transformation initiatives can drive efficiency and intelligence in public service delivery [12]. In addition, the shift from bureaucracy to citizen centricity, facilitated by digital transformation, has led to the deployment of digital capabilities to improve customer experience in public service organizations [14]. Research has demonstrated that implementing collaborative governance in digital transformation may enhance the public value of services by altering the ways in which the government and society interact.…”
Section: Benefits Of Digitalization In Public Service Deliverymentioning
confidence: 99%
“…Furthermore, the implementation of digital transformation in major urban areas is crucial for achieving the advantages of user-friendly and citizen-centric services, eventually leading to an enhanced quality of life and a more favorable business climate [13]. In addition, the shift from bureaucracy to citizen centeredness through digital transformation strategies is instrumental in enhancing customer experience and improving public service delivery [14]. This transformation requires the government to fully utilize technological advances to improve public services and government administration, thus emphasizing the need for a comprehensive approach to digital transformation [15].…”
Section: Technology and Governance Solutions To Address Challenges In...mentioning
confidence: 99%
See 3 more Smart Citations